Vaccine Efficacy of Recombinant Plasmodium falciparum Merozoite Surface Protein 1 in Malaria-Naive, -Exposed, and/or -Rechallenged Aotus vociferans Monkeys - Egan, Andrea F. (American Society for Microbiology, 2000)
Protection against a lethal challenge infection of Plasmodium falciparum was elicited in malaria-naive Aotus vociferans monkeys by vaccination with the C terminus 19-kDa protein of the major merozoite surface protein (MSP-1(19)) fused to tetanus toxoid universal T-cell epitopes P30 and P2. Three of four monkeys were protected against a 10(4)-parasite challenge. Four monkeys were challenged with 10(5) parasites; one self-cured the infection, two were protected against high parasitemia (<2%) but were treated for severe anemia (hematocrit of <25%), and the fourth was not protected. In this model system, anemia appears to be a manifestation of incomplete protection (prolonged low-level parasitemia). Enzyme-linked immunosorbent assay (ELISA) antibody titers correlated with protection. Antibodies from some protected monkeys inhibited secondary processing of MSP-1(42) to MSP-1(33) and MSP-1(19). To mimic the repeated reinfections seen in regions where malaria is endemic, a second malaria parasite challenge was administered 4 months later. All P30P2MSP-1(19)-vaccinated monkeys were protected; thus, a single challenge infection may underestimate vaccine efficacy. ELISA antibody titers correlated with protection against a second infection but had decreased compared to the first challenge. As most target populations for asexual blood-stage malaria vaccines will have been exposed to malaria parasites, a malaria parasite-exposed monkey was vaccinated with P30P2MSP-1(19). This monkey was completely protected, while a malaria parasite-naive P30P2MSP-1(19)-vaccinated monkey self-cured a low-grade parasitemia. Prior malaria parasite infection primed the production of anti-native MSP-1(19) antibodies, which were boosted by vaccination with recombinant P30P2MSP-1(19). Preliminary data suggest that immunogenicity studies of vaccines designed for malaria parasite-exposed populations should also be conducted in malaria parasite-exposed subjects.